Acidified Biochar Confers Improvement in Quality and Yield Attributes of Sufaid Chaunsa Mango in Saline Soil - Javed Iqbal; Sidra Kiran; Shabir Hussain; Rana Khalid Iqbal; Umber Ghafoor; Uzma Younis; Tayebeh Zarei; Misbah Naz; Sevda Ghasemi Germi; Subhan Danish; Mohammad Javed Ansari; Rahul Datta (Horticulturae, 2021)
Mango fruit quality plays a significant role in fruit storage. It also directly affects the economic value of fruit in the national and international markets. However, deterioration of soil health due to low organic matter is a major hurdle for mango growers. Scientists suggest incorporation of organic matter. However, high temperature and low precipitation lead to oxidation of organic residues in soil. On the other hand, biochar is gaining the attention of growers due to its resistance against decomposition. It can improve soil physicochemical attributes. Limited literature is available regarding biochar effects on the quality attributes of mango. Therefore, the current study was planned to investigate the effects of acidified biochar on mango quality and yield attributes in alkaline soil. Five levels of biochar, i.e., 0, 5, 10, 20 and 40 Mg/ha, were applied in a randomized complete block design (RCBD). Results showed that 20 and 40 Mg/ha acidified biochar significantly enhanced fruit retention, sugar contents, ash contents and TSS of mango compared to control. A significant increase in mango fruit weight and yield per plant validated the efficacious role of 40 Mg/ha acidified biochar over control. Furthermore, the maximum significant decrease in fruit juice acidity signified the imperative functioning of 40 Mg/ha acidified biochar in alkaline soil. In conclusion, 40 Mg/ha acidified biochar application can improve mango quality and yield attributes in alkaline soil. More investigations on different soil types, climatic zones and mango varieties are recommended to declare 40 Mg/ha acidified biochar as the best treatment for improvement in the quality and yield of mango fruit in alkaline soils.